LEGAL STATUS OF LAND RIGHTS IN FOREST AREA CLAIMS POST CONSTITUTIONAL COURT DECISION NUMBER 34/PUU-IX/2011 - Sadino, Sadino; Machmud, Aris (Jurnal Pembaharuan Hukum, 2024)
The formulation of the problem in this research is how the government should implement the Constitutional Court Decision regarding forest control by the state in protecting the constitutional rights of affected citizens. This research uses a form of normative legal research with a statutory regulatory approach related to the process of determining an area or land as a forest area. The result is that the state’s claims to areas that have customary law rights must be protected, respected and fulfilled by the rights of customary law communities; as long as the rights of customary communities actually exist and their existence is recognized. Constitutional Court Decision No. 34/PUU-IX/2011 revised Article 4(3) of Forestry Law No. 41/1999, impacting subsequent forestry legislation, like Law No. 11/2020. It upholds indigenous community rights, granted based on statutes and without national interest conflicts. If such rights exist, the government must first negotiate fair settlements with rightful holders. Thus, these communities rights are granted based on the provisions of statutory regulations invitation and does not conflict with national interests according to the Constitutional Court Decision.